Pengaruh IPM, Tenaga Kerja dan Ekspor Terhadap Pertumbuhan Ekonomi Di Provinsi Papua - Anita Apriani (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
Economic growth is an important discussion that is always studied continuously every year. This is an important task that aim of regional government in order to grow the regional economy. The aim of this research is to determine the factors that can trigger economic growth in Papua Province. The variabels used in this research include labor, human development index, exports and economic growth. The research method uses secondary data from the Central Statistics Agency and is processed using multiple linear regression. The research results show that the Human Development Index has a positive and significant effect on the economic growth of Papua Province. Meanwhile, Labor and Exports have a positive but not significant effect on the economic growth of Papua Province. The novelty of this research is that the data used is the latest data adjusted to current year data and research variables that have not been studied in Papua Province as a whole.